Pengembangan Media Pembelajaran Berbasis Wordwall dalam Pembelajaran Matematika Kelas 3 di MI Salafiyah 1 Kauman - I’anatul Ashriyah; Umi Mahmudah (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
This study aims to develop learning media based on the Wordwall application in mathematics learning for grade 3 at MI Salafiyah 1 Kauman. The background of this study is the low interest and motivation of students in participating in mathematics learning, which is caused by less interesting learning methods and the lack of use of interactive media. By utilizing the Wordwall application, it is expected to increase student involvement through fun educational games. The method used in this study is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The development process begins with needs analysis, learning media design, media development using the Wordwall application, media implementation in learning, and evaluation of the effectiveness of the media developed. The results of the study showed that the Wordwall-based learning media developed had high validity with an average score of 90% from material and media experts. The practicality of the media was also obtained with an average score of 85% from teachers and students. The trial of media implementation in mathematics learning showed an increase in student motivation and learning outcomes. So, students will be more active in participating in learning and show a better understanding of the material being taught. Thus, Wordwall-based learning media has proven effective in increasing the motivation and learning outcomes of grade 3 students at MI Salafiyah 1 Kauman.